A new species of Hohenbergia (Bromeliaceae) endemic to the Dolphin Head Mountains in western Jamaica - Aguirre-Santoro, Julián; Campbell, Keron C. St. E.; Proctor, George R. (Phytotaxa, 2016)
Recent botanical expeditions to the Dolphin Head Mountains in western Jamaica allowed the collection of different specimens of a new species, Hohenbergia rohan-estyi, an enigmatic plant that resembles the also Jamaican-endemic H. negrilensis. In this study, we describe H. rohan-estyi and include notes on its geographical distribution, habitat, conservation status and taxonomy. The length of the stipes and number of flowers per spike permit the differentiation of H. rohan-estyi from H. negrilensis. In addition, the geographic distributions of these two species do not overlap, as H. rohan-estyi inhabits mountainous forests of the Dolphin Head region while H. negrilensis occurs in coastal areas of western Jamaica. Finally, H. rohan-estyi is the third species of Hohenbergia reported as endemic to the Dolphin Head Mountains, indicating the importance of this area in the evolution and conservation of the genus in Jamaica and the Caribbean.